Guinea- Bissau : Fifth Review Under the Extended Credit Facility Arrangement, Request for Extension and Augmentation of Access, and Financing Assurances Review-Press Release and Staff Report. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2018)
A fragile state, Guinea-Bissau has maintained robust growth at around 6 percent for the past three years despite a political crisis that led to multiple changes of government and absence of a functioning parliament for most of the period. A recent consensus-based appointment of a new Prime Minister and agreement to undertake parliamentary elections in November 2018 are relieving political tensions.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet